Estimating the incapacitation effect among first-time incarcerated offenders - Al Weswasi, Enes (European journal of criminology, 2024)
Objectives: To estimate how many offenses are averted through the incapacitation of first-time incarcerated offenders with sentences of two years or less. Methods: The counterfactual challenge of estimating criminal acts that would have been committed had the offender not been incarcerated is approached utilizing a matching design. Data comprise all offenders convicted in Sweden in 2018, matched on a vector of time-stable and time-varying covariates drawn from an extensive set of Swedish registers. Each incarcerated offender is matched to a nonincarcerated offender whose offending frequency is used to infer the incapacitation effect. Full sample estimates are provided as well as subgroup estimates for males, females, and various risk groups. Results: The annual incapacitation effect for first-time incarcerated offenders is estimated to be 0.53 when measured as the number of averted convictions and 1.14 when measured as the number of averted offenses that would have resulted in a conviction. For males, the annual number of convictions averted through incapacitation is 0.51, and for females 0.37. For the highest risk group, the annual number of averted convictions is 1.22, and the number of averted offenses resulting in conviction is 2.55. For offenders in the low-to-medium risk groups, the corresponding figures are approximately 0.31 averted convictions and approximately 0.68 averted offenses. Conclusion: For first-time incarcerated offenders, the incapacitation effect is modest and the heterogeneous effects found across different risk groups warrant considering whether the crime-preventive effect is sufficiently large for low-risk inmates and whether noncustodial sanctions might constitute an alternative that would ease overcrowding without producing any considerable risk for costs in terms of recidivism.